Safety and tolerability of nintedanib in patients with idiopathic pulmonary fibrosis in the USA. Issue 1 (27th July 2018) - Noth, Imre; Oelberg, David; Kaul, Manika; Conoscenti, Craig S.; Raghu, Ganesh
Nintedanib has been approved for the treatment of idiopathic pulmonary fibrosis (IPF) in more than 60 countries, including the USA [1]. In the two phase III INPULSIS trials, nintedanib reduced disease progression by reducing decline in forced vital capacity [2]. Most patients were able to manage the side-effects of nintedanib, with 19.3% of patients treated with nintedanib versus 13.0% treated with placebo permanently discontinuing the study medication due to adverse events. The most frequent adverse events were gastrointestinal, particularly diarrhoea. The proportion of patients who had one or more serious adverse events was similar between nintedanib and placebo (30.4% versus 30.0%). The safety and tolerability profile of nintedanib in patients with IPF in the clinical setting is consistent with the product label http://ow.ly/Nulb30jPAld